Anxiety in Spanish EFL University Lessons: Causes, Responsibility Attribution and Coping - Arnaiz, Patricia; Pérez-Luzardo, Jessica (Studia Anglica Posnaniensia, 2014)
Few studies have focused on the anxiety experienced by learners of English as a foreign language in the context of Spanish universities. This study reports on the findings of an investigation into the sources of 216 Spanish university students’ anxiety and incorporates two underexplored aspects in this area, namely, the responsibility students attribute to different agents and the perception students have of their own ability to cope during an anxiety episode. A qualitative/quantitative design was used. Results indicated that the primary source of anxiety related to the speaking skill. Quantitative analyses revealed that learners place the main responsibility for their anxiety on themselves and that women hold themselves responsible for their anxiety to a greater degree than men. The perceived coping ability of men and women was ranked below ‘fair’. Theoretical and practical implications are discussed.